Invincible. 5, The facts of life - Kirkman, Robert; Walker, Corey (Image Comics, 2005)
A collection of comic strips in which Mark Grayson also known as Invincible is still grieving the loss of his father and fighting an unusual parade of villains. But worst of all, Mark has fallen in love and his life is becoming very complex.